2000
DOI: 10.1021/bi001997l
|View full text |Cite
|
Sign up to set email alerts
|

Abietadiene Synthase from Grand Fir (Abies grandis):  Characterization and Mechanism of Action of the “Pseudomature” Recombinant Enzyme

Abstract: The oleoresin secreted by grand fir (Abies grandis) is composed of resin acids derived largely from the abietane family of diterpene olefins as precursors which undergo subsequent oxidation of the C18-methyl group to a carboxyl function, for example, in the conversion of abieta-7,13-diene to abietic acid. A cDNA encoding abietadiene synthase has been isolated from grand fir and the heterologously expressed bifunctional enzyme shown to catalyze both the protonation-initiated cyclization of geranylgeranyl diphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
141
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 117 publications
(150 citation statements)
references
References 51 publications
8
141
0
1
Order By: Relevance
“…11 Reactions were initiated by addition of [15-3 H]ent-copalyl PP (5), 14e and [14-3 H]ent-kaurene was isolated by extraction and analyzed by liquid scintillation counting. 11,43 (Table 3) Studies with native KS partially purified from wild cucumber (Marah macrocarpus) seeds demonstrated that ring rearrangement occurs during the enzyme catalyzed cyclization of entcopalyl PP. 10a Stereo-electronic considerations dictate that the ring D rearrangement cannot be concerted with the preceding cyclization 6 → 7 to the beyeranyl + intermediate.…”
Section: Inhibition Of Ent-kaurene Synthasementioning
confidence: 99%
See 1 more Smart Citation
“…11 Reactions were initiated by addition of [15-3 H]ent-copalyl PP (5), 14e and [14-3 H]ent-kaurene was isolated by extraction and analyzed by liquid scintillation counting. 11,43 (Table 3) Studies with native KS partially purified from wild cucumber (Marah macrocarpus) seeds demonstrated that ring rearrangement occurs during the enzyme catalyzed cyclization of entcopalyl PP. 10a Stereo-electronic considerations dictate that the ring D rearrangement cannot be concerted with the preceding cyclization 6 → 7 to the beyeranyl + intermediate.…”
Section: Inhibition Of Ent-kaurene Synthasementioning
confidence: 99%
“…43 The production of ent-kaurene was quantified by extracting the incubation solutions with hexanes and passing the organic extracts through short columns of MgSO 4 and silica gel to dry them and to remove any oxygenated diterpenoids resulting from non-specific solvolysis prior to liquid scintillation counting. 43 Inhibition studies were carried out with saturating amounts of substrate (1.5 μM [15-3 H]ent-copalyl PP) and varying amounts of inhibitor, and in the case of 13 it was necessary to add substrate directly after inhibitor to detect any enzymatic activity. The resulting data were fit to an exponential equation using KaleidaGraph 4.0 (Synergy Software) to determine IC 50 values as previously described.…”
Section: Inhibition Of Ent-kaurene Synthasementioning
confidence: 99%
“…Interestingly, the products of AgAS were subsequently demonstrated to be sensitive to the assay workup conditions; when passed through silica gel and MgSO 4 prior to GC-MS analysis, abietadiene was the major product (9). However, without this treatment step, levopimaradiene, abietadiene, and neoabietadiene were seen in nearly equal amounts, along with minor amounts of palustradiene (6). This inconsistency was hypothesized to be the result of isomerization of levopimaradiene and neoabietadiene to abietadiene with the silica gel and MgSO 4 treatment (6) but was not investigated further until now.…”
mentioning
confidence: 99%
“…This inconsistency was hypothesized to be the result of isomerization of levopimaradiene and neoabietadiene to abietadiene with the silica gel and MgSO 4 treatment (6) but was not investigated further until now. Consequently, AgAS was described as a multi-product diterpene synthase (6).…”
mentioning
confidence: 99%
“…4 In addition, AgAS has been shown to produce sandaracopimara-8(14),15-diene (7) as a minor component (∼2%) of its product output, 8 suggesting 7 as a potential stable intermediate. However, labeling studies demonstrated intramolecular proton transfer, 9 and 7 is not converted to abietadienes by AgAS, 2 indicating that if 7 is a true intermediate it is only transiently formed en route to abietadienes in the AgAS active site. The catalyzed intramolecular proton transfer entails a shift from tertiary (5a + ) to secondary carbocation that is driven, at least in part, by ion pairing of the resulting isopimar-8(14)-en-15-yl + (5b + ) with the pyrophosphate anion released by initiating ionization of CPP (6).…”
mentioning
confidence: 99%